Hubungan Kualitas Resume Medis dan Ketepatan Koding Kasus Pneumonia dengan Hasil Klaim di RSIJ Sukapura - Sansy Dua Lestari Putri Azah; Husni Abdul Muchlis; Hosizah Hosizah; Witri Zuama Qomarania (Politeknik Negeri Jember, 2026)
Hospitals submit BPJS Health insurance claim documents to obtain reimbursement for healthcare services provided. Observations at RSIJ Sukapura identified 32 pending claim files (70%) caused by incomplete documentation of clinical symptoms in medical discharge summaries. This issue led to the revision of the diagnosis code from J18.9 to J22, resulting in reduced claim values and an increased number of pending claims. This study aimed to examine the relationship between the quality of medical discharge summaries, coding accuracy, and claim outcomes among hospitalized pneumonia patients at RSIJ Sukapura. A quantitative study was conducted using a population of 102 pneumonia cases recorded in May 2024. Using purposive sampling, 89 claim files were selected for analysis. The results showed that 71 files (79.8%) had good-quality medical discharge summaries, 75 files (84.3%) demonstrated accurate coding, and 70 files (78.7%) resulted in eligible claims. Multiple logistic regression analysis revealed a significant relationship between the quality of medical discharge summaries, coding accuracy, and claim outcomes (p < 0.001). Good-quality documentation and accurate coding increased the likelihood of producing eligible claims. Therefore, physician education regarding complete documentation in accordance with BPJS Health requirements is recommended to reduce pending claims.